2018
DOI: 10.1002/eat.22995
|View full text |Cite
|
Sign up to set email alerts
|

Imagery rescripting in individuals with binge‐eating behavior: An experimental proof‐of‐concept study

Abstract: Objective: Mental imagery is more strongly related to emotions than verbal cognitions. Binge eating is associated with dysfunctional emotional regulation. However, cognitive therapy techniques have focused on verbal cognitions. This proof-of-concept study compares a traditional cognitive therapy technique, cognitive restructuring (CR), with imagery rescripting (IR) in individuals with binge-eating disorder or bulimia nervosa.Method: Thirty-six participants were asked to recall an idiosyncratic mental image of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…Most recently, Dugué, Renner, Austermann, Tuschen‐Caffier, and Jacob (2019) compared a single session of IR versus cognitive restructuring among 36 individuals with binge‐eating disorder or BN. All participants were instructed to recall a social rejection situation.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Dugué, Renner, Austermann, Tuschen‐Caffier, and Jacob (2019) compared a single session of IR versus cognitive restructuring among 36 individuals with binge‐eating disorder or BN. All participants were instructed to recall a social rejection situation.…”
Section: Introductionmentioning
confidence: 99%
“…Although originally applied to distressing or core dysfunctional memories, in fact, the technique can be applied to any kind of imagery, and the past decade has seen an ever-increasing range of its applications as clinicians and researchers have realised the therapeutic possibilities. This has included using imagery rescripting of distressing memories as a stand-alone treatment for depression (Brewin et al 2009), including within the context of a self-help approach (Moritz et al 2018), to voicehearing (Paulik et al 2019) and nightmares (Sheaves et al 2019) in the context of psychosis, to distressing memories in OCD (Basile et al 2018;Veale et al 2015), test anxiety (Maier et al 2020), binge eating disorder (Dugué et al 2019), social anxiety (Norton and Abbott 2016;Wild et al 2007), and much more (see also Morina et al 2017 for a meta-analysis). This increase in clinical applications of imagery rescripting has been accompanied by interest in the underlying mechanisms, investigated in experimental studies (e.g.…”
Section: Dysfunctional Mental Imagerymentioning
confidence: 99%
“…The rescripting can help the patient by offering a fresh perspective on events that happened in the past, eliciting new feelings, identifying unmet needs, and confronting the patient with reality so that a healthy mourning process can ensue. Previous studies indicated imagery as an effective intervention in decreasing negative self‐beliefs in patients with BN compared to a control condition that consisted of verbally examining the effects of beliefs on current functioning (Dugué et al, 2019 ). Imagery rescripting (ImRs) showed good outcomes in terms of short‐term decreased of binge eating and vomiting when conventional CBT had failed (Ohanian, 2002 ) as well as longer term maintenance (Wheatley et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%